Detecção de anomalias em processos do sistema operacional Linux - Araujo, Priscila Vriesman (2017)
The processes provide information about applications, auxiliary and service programs such as network and daemons, managing that is executed in the Operating System. Many processes are required without the prior knowledge that managers can test the system operation. Maintaining integrity, good performance and security assurance are fundamental to a good management of Operating Systems. In data mining, it is considered an anomaly detection technique to identify an action different from normal behavior. Thus, this work presents an anomaly detection model based on the behavior of the Linux Operating System processes.